Advanced microscopic evaluation of parallel type I and type II cell deaths induced by multi-functionalized gold nanocages in breast cancer. Issue 3 (11th January 2019) - Raveendran, Sreejith; Sen, Anindito; Ito-Tanaka, Hiromi; Kato, Kazunori; Maekawa, Toru; Kumar, D. Sakthi
Abstract : This work evaluates the potential of type I and type II cell deaths in parallel killing of breast cancer cells to mitigate the induced chemoresistance caused. Abstract : Despite aggressive surgical resections and combinatorial chemoradiations, certain highly malignant populations of tumor cells resurrect and metastasize. Mixed-grade cancer cells fail to respond to standard-of-care therapies by developing intrinsic chemoresistance and subsequently result in tumor relapse. Macroautophagy is a membrane trafficking process that underlies drug resistance and tumorigenesis in most breast cancers. Manipulating cellular homeostasis by a combinatorial nanotherapeutic model, one can evaluate the crosstalk between type I and type II cell death and decipher the fate of cancer therapy. Here, we present a multi-strategic approach in cancer targeting to mitigate the autophagic flux with subcellular toxicity via lysosome permeation, accompanied by mitochondrial perturbation and apoptosis. In this way, a nanoformulation is developed with a unique blend of a lysosomotropic agent, an immunomodulating sulfated-polysaccharide, an adjuvant chemotherapeutic agent, and a monoclonal antibody as a broad-spectrum complex for combinatorial nanotherapy of all breast cancers. To the best of our knowledge, this manuscript illustrates for the first time the applications of advanced microscopic techniques such as electron tomography, three-dimensional rendering and segmentation of subcellular interactions, and fate of the multifunctional therapeutic gold nanocages specifically targeted toward breast cancer cells.